Cheerful chick - Brockenbrough, Martha (Arthur A. Levine Books, an imprint of Scholastic Inc., 2019)
Told in rhyme, Chick hatched from her egg wanting to cheer, and lead a barnyard cheering team, but Pig, Cow, and the other animals are not interested--so unless she can find some other cheerers Chick will just have to cheer alone.